Mesin Perajang Singkong Kapasitas 100 kg/jam - Saban Ridwan (UNIVERSITAS ISLAM MALANG, 2022)
There are many Micro, Small and Medium Enterprises which are often called MSMEs in the food processing sector in Sumbermanjing Kulon, one of which is cassava processing MSMEs in Pagak Regency. Cassava is an agricultural commodity which is a typical local product of Sumbermanjing Kulon, especially in Pagak Regency. MSMEs have proven to be the pillars of the national economy during the global economic crisis, for that they must be seriously considered and developed. Workers in cassava processing SMEs often experience several complaints. This study aims to analyze the complaints and needs of workers in cassava processing MSMEs, then design a cassava chopper tool that meets ergonomic aspects and increases the productivity of the cassava processing MSMEs. Analysis of workers' complaints is done by distributing questionnaires about the comfort level of the work process. Furthermore, it is translated into the design of the cassava chopper tool in the form of computer design drawings. After that, the process of making the design of the tool and testing its productivity. The driving motor used is a 1 PK electric motor. Based on the results of the analysis of the complaints and needs of workers in cassava processing SMEs, it was found that the correlation between the needs of workers and the value of technical characteristics with the results obtained was 73.95. While the results of experiments that have been carried out on a cassava chopper machine that has been designed and built that meets ergonomic aspects or the level of comfort, has a productivity level of 100 kg/hour.